Economic and Clinical Impact of Digitally Produced Dentures. (14th May 2021) - Smith, P. Bradford; Perry, Jeffrey; Elza, William
Abstract: Purpose: Digital denture technology has been gradually moving to the mainstream of dentistry over the last 25 years. Implementation of a four‐step system utilizing in‐house CAD/CAM milling technology may create cost savings for the clinical program in a dental university setting. An analysis was completed to evaluate the cost savings, if any, of fabricating complete dentures digitally versus traditionally through an outside lab. Materials and Methods: A large clinic at a North American dental school began fabricating digital dentures in 2019 utilizing the four‐step Ivoclar system. A combination of 3D printing and CAD/CAM milling produced multiple denture products used in the steps of the digital process, including the final milled complete denture. Results: A significant cost savings was achieved, both in terms of material cost and in chair time cost when compared to traditional laboratory fabricated complete dentures. Conclusion: A large clinic at a North American dental school introduced digital denture technology into the student clinical experience. This digital technology has created a cost‐saving benefit when fabricating digital dentures. Using 3D printing for the preliminary steps resulted in substantial cost savings. Fewer visits to complete the denture fabrication steps, along with fewer postinsertion visits, added further savings. Patient satisfaction with the digital denture process has been consistently high, as has student and faculty satisfaction with the final product.